Cationic amino acid uptake constitutes a metabolic regulation mechanism and occurs in the flagellar pocket of trypanosoma cruzi - Miranda, Mariana Reneé (2012)
Trypanosomatids' amino acid permeases are key proteins in parasite metabolism since they participate in the adaptation of parasites to different environments. Here, we report that TcAAP3, a member of a Trypanosoma cruzi multigene family of permeases, is a bona fide arginine transporter. Most higher eukaryotic cells incorporate cationic amino acids through a single transporter. In contrast, T. cruzi can recognize and transport cationic amino acids by mono-specific permeases since a 100-fold molar excess of lysine could not affect the arginine transport in parasites that over-express the arginine permease (TcAAP3 epimastigotes). In order to test if the permease activity regulates downstream processes of the arginine metabolism, the expression of the single T. cruzi enzyme that uses arginine as substrate, arginine kinase, was evaluated in TcAAP3 epimastigotes. In this parasite model, intracellular arginine concentration increases 4-folds and ATP level remains constant until cultures reach the stationary phase of growth, with decreases of about 6-folds in respect to the controls. Interestingly, Western Blot analysis demonstrated that arginine kinase is significantly down-regulated during the stationary phase of growth in TcAAP3 epimastigotes. This decrease could represent a compensatory mechanism for the increase in ATP consumption as a consequence of the displacement of the reaction equilibrium of arginine kinase, when the intracellular arginine concentration augments and the glucose from the medium is exhausted. Using immunofluorescence techniques we also determined that TcAAP3 and the specific lysine transporter TcAAP7 co-localize in a specialized region of the plasma membrane named flagellar pocket, staining a single locus close to the flagellar pocket collar. Taken together these data suggest that arginine transport is closely related to arginine metabolism and cell energy balance. The clinical relevance of studying trypanosomatids' permeases relies on the possibility of using these molecules as a route of entry of therapeutic drugs